2022
DOI: 10.3390/biology11050649
|View full text |Cite
|
Sign up to set email alerts
|

Gene Editing of the Catfish Gonadotropin-Releasing Hormone Gene and Hormone Therapy to Control the Reproduction in Channel Catfish, Ictalurus punctatus

Abstract: Transcription activator-like effector nuclease (TALEN) plasmids targeting the channel catfish gonadotropin-releasing hormone (cfGnRH) gene were delivered into fertilized eggs with double electroporation to sterilize channel catfish (Ictalurus punctatus). Targeted cfGnRH fish were sequenced and base deletion, substitution, and insertion were detected. The gene mutagenesis was achieved in 52.9% of P1 fish. P1 mutants (individuals with human-induced sequence changes at the cfGnRH locus) had lower spawning rates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…This variation may be due to heterozygous individuals lacking stable genetic traits, or off-target integrations in other regions concealing growth advantages in the P 0 generation [50]. cfGnRH-deficient channel catfish did not show significant effects in growth and survival throughout a four-year culture compared to the WT fish [19]. However, potential pleiotropic effects could exist when the LH gene is replaced by the As-Cath in our cases.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This variation may be due to heterozygous individuals lacking stable genetic traits, or off-target integrations in other regions concealing growth advantages in the P 0 generation [50]. cfGnRH-deficient channel catfish did not show significant effects in growth and survival throughout a four-year culture compared to the WT fish [19]. However, potential pleiotropic effects could exist when the LH gene is replaced by the As-Cath in our cases.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, representative examples have illustrated that reproductive confinement is promising in model and cultured fish by knocking out/disrupting gonadal development-related genes [23,[63][64][65][66]. Recently, Qin et al [19] demonstrated that the reproduction-blocked channel catfish are sterile, and this reproductive confinement can be lifted through hormone therapy with LHRHa. In this study, the dose of 1600 IU/kg HCG coupled with 50 μg/kg LHRHa can restore fecundity at the highest level in comparison to other hormone treatments, but this improvement is not significant from that of 1200 IU/kg HCG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes encoding these three key hormones are pivotal in gonadal maturation. Qin et al (2016) and Qin et al (2022) revealed that channel catfish with LH- or GnRH-mutations had a reduced fertility compared to wild-type individuals, indicating that knocking out or disrupting the LH or GnRH gene can induce reproductive confinement. Docosahexaenoic acid (DHA), an omega-3 fatty acid, is essential for the development of human eye and nerve tissues (Judge et al, 2007), and the DHA biosynthesis pathway requires the elongase gene Elovl2 to function (Gregory and James, 2014).…”
Section: Discussionmentioning
confidence: 99%